CORRUPTION, EASE OF DOING BUSINESS, FOREIGN DIRECT INVESTMENT, AND COMPETITIVENESS IN ASEAN COUNTRIES - Azwardi Azwardi; Wahyu Aji Wijaya (Integrated Journal of Business and Economics)
This study aims to analyze perceptions of corruption, ease of doing business, foreign investment on national competitiveness in ASEAN countries. This study uses panel data analysis with CEM, FEM, and REM approaches by using research samples from 10 countries that are members of the ASEAN organization. The results showed that Corruption Perception (CPI), ease of doing business, and Foreign Direct Investment had a significant and positive effect on National Competitiveness in ASEAN Countries.